1999
DOI: 10.1021/bi9822022
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Transcription and Translation in Dictyostelium discoideum Nuclei

Abstract: The nuclei of Dictyostelium discoideum cells have been found to contain polyribosomes active in protein synthesis. mRNA molecules enter nuclear polyribosomes while they are still being synthesized. "Non sense mediated mRNA decay" occurs in the nucleus, through the interaction of the mRNAs containing a nonsense codon with newly formed nuclear ribosomes, rather than with cytoplasmic ribosomes, as previously generally supposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Fresh evidence for nuclear translation has come from recent experiments with the slime mold Dictyostelium discoideum, in which polyribosome-like entities were identified in nuclei, based on their sedimentation in sucrose gradients, their ability to be pulse-labeled with [ 3 H]uracil, and their sensitivity to the protein synthesis inhibitor puromycin. (80) These putative nuclear polyribosomes cosedimented with both nascent mRNAs and nascent polypeptides. Based on this set of correlative data, it was concluded that transcription and translation are probably coupled in D. discoideum.…”
Section: Translation Factors Functioning In the Nucleus?mentioning
confidence: 99%
“…Fresh evidence for nuclear translation has come from recent experiments with the slime mold Dictyostelium discoideum, in which polyribosome-like entities were identified in nuclei, based on their sedimentation in sucrose gradients, their ability to be pulse-labeled with [ 3 H]uracil, and their sensitivity to the protein synthesis inhibitor puromycin. (80) These putative nuclear polyribosomes cosedimented with both nascent mRNAs and nascent polypeptides. Based on this set of correlative data, it was concluded that transcription and translation are probably coupled in D. discoideum.…”
Section: Translation Factors Functioning In the Nucleus?mentioning
confidence: 99%
“…However, it was shown more than two decades ago that a small fraction of amino acids are incorporated into polypeptides in the nucleus, but in those experiments a possible cytoplasmic contamination could not be excluded (Goidl and Ross 1978). More recently it was reported that in Dictyostelium discoideum nuclei nascent molecules of specific mR-NAs are associated with polyribosomes active in protein synthesis (Mangiarotti 1999). Because these results were obtained with isolated nuclei, it is difficult to exclude any cytoplasmic contamination.…”
Section: Introductionmentioning
confidence: 98%
“…Mangiarotti (1999) provided evidence for the coupling of transcription and translation in Dictyostelium nuclei. Iborra et al (2001) reported that nascent polypeptides accumulate in the nucleus of HeLa cells, also concluding that transcription and translation are coupled.…”
Section: Introductionmentioning
confidence: 98%